Localization instabilities due to damage and fracture propagation - Tabbara, Mazen R. (2017)
In recent research it has become clear that localization of damage due to strain softening as well as propagation of interactive cracks can result in bifurcations of the loading path characterized by localization of damage or fracture. Analysis of unnotched tension specimens by means of a particle model reveals a development of asymmetric response path after the peak load. A separate analysis based on inelastic stability theory is applied to an edge-notched tension specimen. It is found that the response path corresponding to symmetric propagation of both cracks is unstable and the propagation tends to localize into a single crack tip.